Urgensi Peningkatan Kesejahteraan Bagi Profesi Jurnalis Sebagai Bentuk Pemenuhan Hak Tenaga Kerja di Indonesia - Sandiah, Rara Siti (Media Hukum Indonesia (MHI), 2024)
Journalists play an important role in democracy and society, yet they often work in unfavorable conditions with low salaries, long working hours, and lack of social protection. The purpose of this research is to contribute to understanding the complexity of journalists' welfare issues in Indonesia, as well as to encourage concrete efforts to improve legal protection of labor rights for the journalist profession. The research method used is normative legal research method. The results show that the factors causing the lack of journalists' welfare include exploitation by media companies, the lack of role of trade unions and journalists' low understanding of their rights. For this reason, it requires an active role and joint commitment from various parties such as the government, media companies, journalist organizations, and journalists themselves who need to understand and protect labor rights.